Joyful reunion. 2 - Feitianyexiang; Mandelo, Lee (Fei, Tian Ye Xiang. Joyful reunion, 2025)
"In the wake of the fall of Shangjing, Duan Ling flees the city, setting out on a desperate journey to reunite with his father in the imperial capital of Xichuan. When he arrives, however, nothing is as he hoped. After losing nearly everything-including his life-the despairing Duan Ling is rescued by Wu Du, a down on his luck poison master and assassin. Terrified of being killed if his true identity is discovered, Duan Ling assumes a false name and scrapes out a meager life in Wu Du's shadow. Yet the more he gets to know the prickly assassin, the more Duan Ling feels his rescuer can be relied on. When Wu Du's master sends the two on a dangerous mission together, Duan Ling must decide: Can this man who saved his life be trusted with it?"